Gestation-specific reference intervals for right and left ventricular ejection force from 12 to 40 weeks of gestation. (16th November 2010) - Parasuraman, R; Osmond, C; Howe, DT
Abstract : Objectives: Ejection force of the fetal cardiac ventricles has only been assessed from 18 weeks of gestation. Hence, the authors aimed to establish gestation specific reference intervals for ventricular ejection force (VEF) from 12 to 40 weeks of pregnancy. Methods: In a cross-sectional observational study of singleton pregnancies examinations were performed in 237 women evenly distributed across each week of pregnancy from 12 to 40 weeks. Each mother was scanned once. For the aortic and pulmonary valves, the time to peak velocity (TPV) and the average (TAV) and peak flow velocity (PSV) in systole was measured. For each the authors averaged values from three consecutive complexes. The outlet valve diameters were measured and the VEF on both the right and left sides were calculated using the formula VEF= (1.055 × valve area × TPV × TAV) × (PSV/TPV)1 where 1.055 represents the density of blood. Results: The authors present centile graphs for right and left VEF. The authors demonstrated that the ventricular force on both right and left sides increases with advancing gestational age. Conclusion: Fetal cardiac physiology can be studied and Doppler indices reliably measured as early as the late first trimester of pregnancy. VEF has been shown to be reduced in growth restricted babies and study of this may eventually provide better understanding of changes which may predispose to adult cardiac disease.